2018
DOI: 10.1038/s41467-018-02864-2
|View full text |Cite
|
Sign up to set email alerts
|

Steric exclusion and protein conformation determine the localization of plasma membrane transporters

Abstract: The plasma membrane (PM) of Saccharomyces cerevisiae contains membrane compartments, MCC/eisosomes and MCPs, named after the protein residents Can1 and Pma1, respectively. Using high-resolution fluorescence microscopy techniques we show that Can1 and the homologous transporter Lyp1 are able to diffuse into the MCC/eisosomes, where a limited number of proteins are conditionally trapped at the (outer) edge of the compartment. Upon addition of substrate, the immobilized proteins diffuse away from the MCC/eisosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 48 publications
8
101
1
Order By: Relevance
“…Profiles across the PM indicated that Mup1 was localized further away from the cell center than Pil1. This localization is even better seen by super‐resolution microscopy (Bianchi et al , ) and is typical for proteins of the MCC, which likely do not enter the furrows formed by eisosomes (Douglas & Konopka, ). By combining total internal reflection fluorescence microscopy (TIRFM) and 2D deconvolution, we confirmed the localization of Mup1 to the MCC, but also found weaker staining in a network‐like distribution connecting the patches (see asterisk in the lower plot of Fig A).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Profiles across the PM indicated that Mup1 was localized further away from the cell center than Pil1. This localization is even better seen by super‐resolution microscopy (Bianchi et al , ) and is typical for proteins of the MCC, which likely do not enter the furrows formed by eisosomes (Douglas & Konopka, ). By combining total internal reflection fluorescence microscopy (TIRFM) and 2D deconvolution, we confirmed the localization of Mup1 to the MCC, but also found weaker staining in a network‐like distribution connecting the patches (see asterisk in the lower plot of Fig A).…”
Section: Resultsmentioning
confidence: 76%
“…So far we have discussed how Mup1 clusters in MCC patches, but we have not defined the region of the PM into which it relocates upon its release from the MCC. To better define the network‐like domain where Mup1 resides after substrate addition (Fig ), we tested its colocalization with the MCP marker Pma1 (Fig A), which is often used as a general marker for all PM areas outside of the MCC (Bianchi et al , ). Interestingly, while we confirmed the perfect separation of the MCC and the MCP (Fig A), we found that even after MCC exit, Mup1 clearly segregated from Pma1 (Fig A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial mapping and functional analyses of surface cargoes have recently shown lipid domains, termed eisosomes, harbour surface proteins and antagonize their endocytosis (Bianchi et al, 2018;Busto et al, 2018;Gournas et al, 2018;Moharir et al, 2018). Eisosomal regulation of surface proteins in response to glucose starvation is implied from PIL1, which encodes the structural Pil1 protein required for the proper formation of eisosomes (Walther et al, 2006), being identified as a potential Mig1 target (Supplemental Table 1).…”
Section: Eisosomal Reorganisation Sequesters Cargo During Glucose Stamentioning
confidence: 99%
“…Surface cargoes are also organised spatially within the plasma membrane. For example, in yeast, although membrane proteins are dispersed throughout the surface, certain cargoes, including nutrient transporters, also diffuse into PM invaginations termed eisosomes (Bianchi et al, 2018;Grossmann et al, 2008;Spira et al, 2012). Eisosomes have recently been shown to regulate both lipids and proteins at the surface in response to stress (Babst, 2019).…”
Section: Introductionmentioning
confidence: 99%